Inhibition of Cigarette Smoke Induced-inflammation and Oxidative Damage by Caffeic Acid Phenethyl Ester in A549 Cells - Kucukgul, Altug (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: The main objective of this study was to evaluate the effect of antioxidative and antiapoptotic effects and underlying molecular mechanisms of caffeic acid phenethyl ester (CAPE) on human lung epithelial cells exposed to cigarette smoke (CS). Materials and Methods: Human alveolar epithelial A549 cells were exposed to CS and treated with various concentrations of CAPE for 24 h, and their effective concentrations were identified by cell viability assay (MTT). Antioxidant and anti-inflammatory effect of CAPE on nuclear erythroid related factor-2 (Nrf2) and nuclear factor-Ä¸Î² (NF-Ä¸Î²) protein levels were analyzed by Western blotting. Furthermore, caspase 8 gene expression level was analyzed by reverse transcription-quantitative polymerase chain reaction. Results: Low concentration CAPE pretreatment rescued 52% of CS-exposed A549 cells from death. CS upregulated gene expression level of caspase 8 by 4.28 fold. However, 2.5 Î¼M CAPE pretreatment increased caspase 8 level by 52%. CS exposure also elevated NF-Ä¸Î² (p65) protein level by 70%, however, CAPE pretreatment significantly reversed this activation. While CS exposure decreased Nrf2 protein levels by 48% as compared with the control group, CAPE pretreatment increased Nrf2 protein level two folds approximately according to CS group. Discussion: CAPE markedly decreased inflammatory transcription factor NF-kB and increased antioxidant response element Nrf2 protein expression levels in CS-exposed human alveolar cells. According to the data obtained from this study, CAPE could be used as a strategic alternative to support treatment of inflammatory and oxidative stress-induced lung diseases.